The Finnish Personalization Paradox: Party Control in Europe’s Most Open Proportional System - Kandić, Uroš; Hodzic, Jasmin (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The Finnish electoral system represents a unique case among contemporary European democracies. Formally, it constitutes one of the most inclusive proportional models for voters and candidates—the Finnish "quasi-list" system enables mandatory preferential voting, legally mandated primary elections, and alphabetical ranking of candidates on party lists. However, empirical data reveals a significant gap between institutional openness and actual personalization. This paper examines a fundamental paradox: how have Finnish political parties, despite the high intra-party efficiency of electoral institutions, managed to maintain dominant control over nomination processes and electoral outcomes? The analysis covers the period from early reforms in 1906-1969, when parties exploited electoral association alliances and multiple candidacies to manipulate the system, to the contemporary model established in 1955 and its subsequent modifications. Applying Shugart’s indices of inter-party and intra-party efficiency, alongside analysis of empirical data from 21st-century electoral cycles, the paper demonstrates that the Finnish system systematically produces hyper-representativeness, while party nomination strategies—from "balanced lists" to "vote magnets"—effectively constrain personalization. The paper contributes to the literature on electoral system personalization by demonstrating that formal institutional openness does not guarantee actual personalization when parties develop sophisticated adaptive strategies. The Finnish case illustrates how historically embedded mechanisms of party control can survive reforms, and how the stability of democratic institutions can be simultaneously both a result of and an obstacle to electoral system change.